Description of the final stadium larvae of Polycanthagyna ornithocephala (McLachlan, 1896) from Taiwan, with a key to the known larvae of the genus (Odonata: Anisoptera: Aeshnidae) - Wong, Kwok-Ching; Yeh, Wen-Chi; Chan, Tsung-Wei (Zootaxa, 2012)
The final stadium larvae of Polycanthagyna ornithocephala is described and compared to those of its congeners occurringin Taiwan. A key is provided to identify the known larvae of three Polycanthagyna species. General habitus of adult and larva are also discussed.